2010
DOI: 10.1098/rsbl.2009.1024
|View full text |Cite
|
Sign up to set email alerts
|

Links between global taxonomic diversity, ecological diversity and the expansion of vertebrates on land

Abstract: Tetrapod biodiversity today is great; over the past 400 Myr since vertebrates moved onto land, global tetrapod diversity has risen exponentially, punctuated by losses during major extinctions. There are links between the total global diversity of tetrapods and the diversity of their ecological roles, yet no one fully understands the interplay of these two aspects of biodiversity and a numerical analysis of this relationship has not so far been undertaken. Here we show that the global taxonomic and ecological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
101
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 18 publications
2
101
1
1
Order By: Relevance
“…As for ecospace use and specialization, Sahney et al (2010) found that global diversity of tetrapod families rose in line with ecospace use, and that these patterns closely match the dominant classes of tetrapods (amphibians in the Palaeozoic, reptiles in the Mesozoic and birds and mammals in the Cenozoic; figure 2). These groups have driven ecological diversity by expansion and contraction of occupied ecospace rather than by direct competition within existing ecospace and each group has used ecospace at a greater rate than their predecessors.…”
Section: Increasing Biodiversity By Regional Endemicity Expansion Ofmentioning
confidence: 96%
See 2 more Smart Citations
“…As for ecospace use and specialization, Sahney et al (2010) found that global diversity of tetrapod families rose in line with ecospace use, and that these patterns closely match the dominant classes of tetrapods (amphibians in the Palaeozoic, reptiles in the Mesozoic and birds and mammals in the Cenozoic; figure 2). These groups have driven ecological diversity by expansion and contraction of occupied ecospace rather than by direct competition within existing ecospace and each group has used ecospace at a greater rate than their predecessors.…”
Section: Increasing Biodiversity By Regional Endemicity Expansion Ofmentioning
confidence: 96%
“…The closest correlations throughout were between global familial diversity and number of ecospace divisions occupied (Spearman's r ¼ 0.97), much higher than had been expected. Thus, tetrapod families may have become more specialized by dividing diets or habitats, but most of their global expansion was mediated by occupation of new ecospace (Sahney et al 2010). This is not a simple consequence of few families per mode, where addition of a new family would demand a new mode-with 1034 families in 75 modes, the mean occupancy is 13.8 families per mode.…”
Section: Increasing Biodiversity By Regional Endemicity Expansion Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Theory of Biological Interaction, incremental change [37] of species is driven by biological interactions of organisms between and within species [38]. Accordingly, we suggest that incremental change of contractual and relational governance (contract, formal control, trust, informal control) is driven by interactions between and within contractual and relational governance.…”
Section: The Theory Of Biological Interactionmentioning
confidence: 99%
“…), incremental changes are not exclusively driven by small scale contextual changes. Instead biological interactions are also a major driver of incremental change [37].…”
Section: The Theory Of Biological Interactionmentioning
confidence: 99%